Profit tax meaning and its accounting organizations in modern Russian practice - Nicolaenkova M. S., Smekalina Y. A. (Scientific community of students, 2016)
This article is devoted to the study of the essence of corporate income tax and its accounting in Russian practice. The first part of the article reveals the evolution of the income tax in the Russian Federation, as well as the competitiveness of the national tax system in the international arena. The second part of the article is devoted to the basic aspects of accounting for the calculation of corporate income tax.
Keywords: конкурентоспособность; бухгалтерский учет; экономический рост; налог на прибыль; налоговая система; государственный бюджет; accounting; competitiveness; income tax; economic growth; tax system; прибыль организаций; state budget; profit organizations